Prothrombin complex concentrates versus fresh frozen plasma for warfarin reversal A systematic review and meta-analysis - Chai-Adisaksopha, Chatree; Hillis, Christopher; Siegal, Deborah M.; Movilla, Ron; Heddle, Nancy; Iorio, Alfonso; Crowther, Mark (Thrombosis and Haemostasis, 2016)
Urgent reversal of warfarin is required for patients who experience major bleeding or require urgent surgery. Treatment options include the combination of vitamin K and coagulation factor replacement with either prothrombin complex concentrate (PCC) or fresh frozen plasma (FFP). However, the optimal reversal strategy is unclear based on clinically relevant outcomes. We searched in MEDLINE, EMBASE and Cochrane library to December 2015. Thirteen studies (5 randomised studies and 8 observational studies) were included. PCC use was associated with a significant reduction in all-cause mortality compared to FFP (OR= 0.56, 95 % CI; 0.37–0.84, p=0.006). A higher proportion of patients receiving PCC achieved haemostasis compared to those receiving FFP, but this was not statistically significant (OR 2.00, 95 % CI; 0.85–4.68). PCC use was more likely to achieve normalisation of international normalised ratio (INR) (OR 10.80, 95 % CI; 6.12–19.07) and resulted in a shorter time to INR correction (mean difference –6.50 hours, 95 %CI; –9.75 to –3.24). Red blood cell transfusion was not statistically different between the two groups (OR 0.88, 95 % CI: 0.53–1.43). Patients receiving PCC had a lower risk of post-transfusion volume overload compared to FFP (OR 0.27, 95 % CI; 0.13–0.58). There was no statistically significant difference in the risk of thromboembolism following administration of PCC or FFP (OR 0.91, 95 % CI; 0.44–1.89). In conclusion, as compared to FFP, the use of PCC for warfarin reversal was associated with a significant reduction in all-cause mortality, more rapid INR reduction, and less volume overload without an increased risk of thromboembolic events.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Factor concentrates; haemorrhage; warfarin; mortality; plasma